On the Inscriptions upon the Stone at Newton Insch, Aberdeenshire, and on the Inscriptions on a sculptured Stone at St Vigean's, Forfarshire (Proceedings of the Society of Antiquaries of Scotland, 1867)
The author argues that Anglo-Saxon runes were used in inscriptions that otherwise used Latin characters or the Norman-French language, based on the preference of the carver. Using this argument he attempts a translation of the Newton Stone suggesting that some Gaelic or Anglo-Saxon characters may have been used alongside the primary Latin inscription. He then goes on to translate the inscription on the stone at St Vigeans using the same methodology.